Asian Indians in Michigan - Helweg, Arthur Wesley, 1940- (Discovering the peoples of Michigan., 2002)
Since 1970, a growing number of Asian Indians have called Michigan home. Representative of the "new immigration," Asian Indians come from a democratic country, are well-educated, and come from middle- and upper-class families. Unlike older immigrant groups, Asian Indians do not form urban ethnic enclaves or found their own communities to meet the challenges of living in a new society. As Arthur W. Helweg shows, Asian Indians contribute to the richness and diversity of Michigan's culture through active participation in local institutions, while maintaining a strong ethnic identity rooted in In